2018
DOI: 10.1016/j.ymthe.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Transduction and Enhanced Spread of a Modified AAV2 Capsid in the Non-human Primate CNS

Abstract: The present study was designed to characterize transduction of non-human primate brain and spinal cord with a modified adeno-associated virus serotype 2, incapable of binding to the heparan sulfate proteoglycan receptor, referred to as AAV2-HBKO. AAV2-HBKO was infused into the thalamus, intracerebroventricularly or via a combination of both intracerebroventricular and thalamic delivery. Thalamic injection of this modified vector encoding GFP resulted in widespread CNS transduction that included neurons in deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 52 publications
3
44
1
Order By: Relevance
“…Together, these two studies illustrate the feasibility of using novel, designer AAV serotypes with a high propensity for axonal transport to distribute genetic cargo throughout brain circuits by targeting specific structures with a high degree of connectivity in the CNS, such as the thalamus and the striatum. For example, in the current study we demonstrated that AAV2.retro efficiently transduces cognitive, sensorimotor, and limbic cortico-basal ganglia circuitry via intra-striatal delivery, and the work by Naidoo and colleagues with AAV-HBKO demonstrated biodistribution throughout a different network of prefrontal, motor, temporal, and subcortical regions following thalamic infusion 48,49 . Taken together, these studies illustrate how widespread transduction patterns can be achieved even in the large NHP brain by selecting a serotype with high propensity for transport and by selectively choosing the site of injection to target specific populations of neuronal afferents/efferents depending on the network of interest or the specific disease being targeted.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Together, these two studies illustrate the feasibility of using novel, designer AAV serotypes with a high propensity for axonal transport to distribute genetic cargo throughout brain circuits by targeting specific structures with a high degree of connectivity in the CNS, such as the thalamus and the striatum. For example, in the current study we demonstrated that AAV2.retro efficiently transduces cognitive, sensorimotor, and limbic cortico-basal ganglia circuitry via intra-striatal delivery, and the work by Naidoo and colleagues with AAV-HBKO demonstrated biodistribution throughout a different network of prefrontal, motor, temporal, and subcortical regions following thalamic infusion 48,49 . Taken together, these studies illustrate how widespread transduction patterns can be achieved even in the large NHP brain by selecting a serotype with high propensity for transport and by selectively choosing the site of injection to target specific populations of neuronal afferents/efferents depending on the network of interest or the specific disease being targeted.…”
Section: Discussionsupporting
confidence: 62%
“…Naidoo and colleagues demonstrated that intra-thalamic delivery of AAV-HBKO expressing eGFP resulted in robust anterograde transport to deep layers of many cortical regions with thalamic efferents including the ACC, DPFC, VPFC, DPMC, VPMC, PMC, SSC, and ITC. The authors also report evidence of moderate retrograde transport to some subcortical structures and to regions of the brain stem and spinal cord 48 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Naidoo and colleagues demonstrated that intra-thalamic delivery of AAV-HBKO expressing eGFP resulted in robust anterograde transport to deep layers of many cortical regions with thalamic efferents including the ACC, DPFC, VPFC, DPMC, VPMC, PMC, SSC, and ITC. The authors also report evidence of moderate retrograde transport to some subcortical structures and to regions of the brain stem and spinal cord 49 . This contrasts with the pattern of nearly exclusive retrograde transport seen here with AAV2.…”
Section: Discussionmentioning
confidence: 87%
“…retro 32 . There are, however, other AAV capsid variants that have been recently reported to also transport robustly in the NHP brain, such as AAV-HBKO 49 . Naidoo and colleagues demonstrated that intra-thalamic delivery of AAV-HBKO expressing eGFP resulted in robust anterograde transport to deep layers of many cortical regions with thalamic efferents including the ACC, DPFC, VPFC, DPMC, VPMC, PMC, SSC, and ITC.…”
Section: Discussionmentioning
confidence: 99%